Intracellular and non-neuronal targets of voltage-gated potassium channel complex antibodies - Lang, B; Makuch, M; Moloney, T; Dettmann, I; Mindorf, S; Probst, C; Stoecker, W; Buckley, C; Newton, C; Leite, I; Maddison, P; Komorowski, L; et al. (BMJ Publishing Group, 2017)
Objectives Autoantibodies against the extracellular domains of the voltage-gated potassium channel (VGKC) complex proteins, leucine-rich glioma-inactivated 1 (LGI1) and contactin-associated protein-2 (CASPR2), are found in patients with limbic encephalitis, faciobrachial dystonic seizures, Morvan’s syndrome and neuromyotonia. However, in routine testing, VGKC-complex-antibodies without LGI1- or CASPR2-reactivities (“double-negative”) are commoner than LGI1- or CASPR2-specificities. Therefore, the target(s) and clinical associations of double-negative antibodies need to be determined. Methods Sera (n=1131) from several clinically-defined cohorts were tested for IgG-radioimmunoprecipitation of 125I-DTX-labelled VGKC-complexes from mammalian brain extracts. Positive samples were systematically tested for live hippocampal neuron reactivity, IgG-precipitation of 125I-DTX and 125I-DTX-labelled Kv1-subunits, and by cell-based assays which expressed Kv1-subunits, LGI1 and CASPR2. Results VGKC-complex-antibodies were found in 162 of 1131 (14%) sera. Ninety of these (56%) had antibodies targeting the extracellular domains of LGI1 or CASPR2. Of the remaining 72 double-negative sera, ten (14%) immunoprecipitated 125I-DTX itself, and 27 (38%) bound to solubilized co-expressed Kv1.1/1.2/1.6 subunits and/or Kv1.2 subunits alone, at levels proportionate to VGKC-complex-antibody levels (r=0.57, p=0.0017). The sera with LGI1- and CASPR2-antibodies immunoprecipitated neither preparation. None of the 27 Kv1-precipitating samples bound live hippocampal neurons or Kv1-extracellular domains, but 16 (59%) bound to permeabilised Kv1-expressing HEK cells. These intracellular Kv1-antibodies mainly associated with non-immune disease aetiologies, poor longitudinal clinical-serological correlations, and a limited immunotherapy-response. Conclusions Double-negative VGKC-complex-antibodies are often directed against cytosolic epitopes of Kv1-subunits, and occasionally against non-mammalian DTX. These antibodies should no longer be classified as neuronal-surface antibodies. They consequently lack pathogenic potential, and do not in themselves support use of immunotherapies.